(untitled) (The International Journal for Scientific Research, 2024)
E-commerce is considered one of the modern phenomena that has significantly impacted businesses, exerting a noticeable influence on corporate social responsibility. The aim of the study was to understand the role of e-commerce in influencing corporate social responsibility through an analysis of a case study on Noon company. The descriptive-analytical methodology was followed, and a questionnaire was used as a data collection tool. A total of 375 questionnaires were distributed, and 352 valid responses were retrieved, resulting in a response rate of 94%. The study results demonstrated that e-commerce plays a crucial role in enhancing the social responsibility of Noon company. Additionally, the results indicated a statistically significant positive impact of e-commerce on the economic, legal, ethical, and humanitarian dimensions of corporate social responsibility. The study recommended that Noon company’s management should raise awareness among its employees about the concept of e-commerce by enabling and training them on specialized e-commerce programs and fostering a social culture conducive to e-commerce. Furthermore, the management should activate electronic payment processes through its website by accepting credit cards, smart cards, or electronic checks, and continue to develop and update the technological infrastructure of Noon company, including e-commerce platforms and secure payment systems, to enhance customer experience and trust.